Evaluasi Sistem Tanggap Darurat Kebakaran Dengan Metode Plan-Do-Check-Action (PDCA) Sebagai Upaya Pencegahan Dan Penanggulangan Bencana Di RS Islam Klaten - Apriyani, Yesi; , Tarwaka, PGDip.Sc., M.Erg; , Rezania Asyfiradayati, SKM., MPH (2017)
Minister of Health Regulation no. 66 year 2016 on Hospital Health and Safety (K3RS) in Article 16 paragraph (1) requires every hospital to implement fire prevention and control. Fires in hospitals in Indonesia have occurred in 2009 and 2015. Klaten Hospital is one of the hospitals that experienced a fire incident in 2009 in pharmaceutical units. The purpose of this research is to determine the effectiveness of fire emergency response system with PDCA method as an effort to prevent and control fire disaster in RSI Klaten. The method used in this research is observation with the type of research used is qualitative research by using critical incident approach. Subject of this research consist of 5 main informant and 1 informant triangulation with purposive sampling technique. The result of this research is the effectiveness of PDCA method as a measuring tool of fire prevention and control effort found non-conformity to K3 policy and commitment and function of gathering point. Based on the identification of potential risk of fire hazard in 7 hospital units it is known that pharmacy unit and laboratory unit have high risk compared to 5 other units. Conclusion in this research is still there are 2 point which have not fulfilled that is socialization of policy and commitment of K3 and switch function of point gathering area. Therefore, the management of Klaten Islamic Hospital is expected to disseminate policies and commitments related to fire emergency response system. Socialization is done in the form of pictures, pamphlets, appeal and restore function of the point area gathered as a means of evacuation of life saving.